Divine evil?: the moral character of the God of Abraham - Bergmann, Michael; Murray, Michael James; Rea, Michael C. (Oxford University Press, 2010)
This title features 11 original essays by philosophers and biblical scholars addressing the character of God as portrayed in the Hebrew Bible. The book includes a critical commentary on each essay by another author, and replies to the critical comments by the original author.